The Settlement of Child Cases in Conflict with the Law in the Concept of Restorative Justice - Muhammad Ridwan Lubis (Jurnal Daulat Hukum, 2022)
This study aims to know the application of the principle of Restorative Justice as an effort to resolve crimes committed by children even though formally and legally regulated clearly and explicitly in Act No. 11 of 2012, but formally problems also arise related to the time when the law was enforced which in Article 108. The approach used in this study is normative juridical. Factors that cause children to commit criminal acts, namely: Endogenous factors are factors that occur because of their own will, family factors, school environment factors and children's play areas, mass media factors, economic factors. Diversion as a step in diverting the settlement of child cases from the criminal justice process to processes outside the criminal justice by prioritizing the Restorative Justice approach which can be carried out by way of deliberation or mediation which emphasizes efforts to restore the family to its original state.